Glia: A Neglected Player in Non-invasive Direct Current Brain Stimulation - Gellner, Anne-Kathrin; Reis, Janine; Fritsch, Brita (Frontiers in Cellular Neuroscience, 2016)
Noninvasive electrical brain stimulation by application of direct current (DCS) promotes plasticity in neuronal networks in vitro and in in vivo. This effect has been mainly attributed to the direct modulation of neurons. Glia represents approximately 50% of cells in the brain. Glial cells are electrically active and participate in synaptic plasticity. Despite of that, effects of DCS on glial structures and on interaction with neurons are only sparsely investigated. In this perspectives article we review the current literature, present own dose response data and provide a framework for future research from two points of view: first, the direct effects of DCS on glia and second, the contribution of glia to DCS related neuronal plasticity.